Floodplain biogeochemical mosaics: A multidimensional view of alluvial soils. Issue 8 (12th August 2014) - Appling, Alison P.; Bernhardt, Emily S.; Stanford, Jack A.
Abstract The alluvial floodplains of large rivers are exceptionally productive and dynamic ecosystems, characterized by a complex mosaic of vegetation at different successional stages overlying soils sorted by historic floods. Natural floodplains are widely credited with efficiently removing nitrogen from surface waters and accumulating carbon in biomass, yet very little floodplain research has examined carbon and nitrogen cycling below surficial soils. We evaluated the extent to which vegetation cover could be used to predict subsurface carbon and nitrogen dynamics and to estimate whole‐floodplain carbon storage and denitrification rates. We dug soil pits under three dominant vegetation communities on a gravel‐bedded floodplain in northwest Montana to the depth of the permanent water table (1–3 m). We compared depth profiles of total and dissolved carbon (C) and nitrogen (N), denitrification potentials (DEAs), organic particulates, moisture, and pH across vegetation types. Near‐surface soils (0–10 cm) of forests had larger C and N pools and DEAs than grasslands or gravel bars, but such vegetation effects dissipated within the upper 50 cm of soil. At depth, spatial heterogeneity in carbon and nitrogen pools and fluxes depended instead on soil texture, and relatively high rates of DEA and carbon storage were measured in zones of buried organic debris. Although C storage and denitrification potential are generally low in subsurface soils, these deep soils might nonetheless contribute substantially to whole‐floodplain C storage and denitrification because of their large volume, high hydrologic connectivity, and heterogeneous biogeochemistry.